Ergonomic Model Based on ISO 45001 and ISO 11228 to increase productivity in a Metalworking Company (SCIÉNDO INGENIUM, 2026)
This study describes the implementation of an ergonomic model based on ISO 45001 and ISO 11228 standards to increase productivity and improve working conditions in a Peruvian metalworking company. A pre-experimental design was used, employing tools such as RULA, REBA, and OWAS to assess working postures and ergonomic risks. After applying the model, a 15.3% increase in efficiency, 16.7% improvement in productivity, and 50% reduction in absenteeism were observed. It is concluded that the systematic application of international standards allows ergonomics to be integrated as a strategic management tool.
Keywords: Ergonomics; ISO 45001; ISO 11228; productivity; occupational health and safety